A Prospective Surveillance of Pharmacovigilance of Psychotropic Medicines in a Developing Country - Lucca, Jisha Myalil (Psychopharmacol Bull, 2016)
AIMS/OBJECTIVES: Psychotropic drugs are associated with significant short-term and long-term safety issues which may affect patients’ mental health, physical health and cost of care. EXPERIMENTAL DESIGNS: This was a prospective study conducted in psychiatry department of a tertiary care hospital. Study included patients of any age and either sex who presented with psychiatric illness as diagnosed by ICD-10 and were receiving at least one psychotropic agent. The study involved both intensive and spontaneous reporting methods to identify ADRs. Causality, Severity, Preventability of reported ADR was assessed using standard scales. PRINCIPLE OBSERVATION: Of 4321 patients reviewed, 1630 patients met study criteria, 990 ADRs were identified from 613 patients at an overall incidence rate of 37.6%. Antidepressants were the commonest group of agents implicated in ADRs (42%) followed by Antipsychotics (41%). Escitalopram (15.9%) and Olanzapine (12.1%) were the most commonly implicated medications. Most commonly involved system organ class was Gastrointestinal system (22.7%) followed by Central and peripheral nervous system (17.8%). Dry mouth (10.2%), weight gain (8.18%) and tremors (5.85%) were the commonly reported ADRs. Female gender (p = 0.002), Co-morbid conditions (p = 0.001) and drug- drug interactions (p = 0.000) were found as risk factors in developing ADRs in psychiatry patients. CONCLUSION: Patients receiving psychotropic medicines need routine monitoring to ensure their safety and adherence.